Pengaruh Kompos, Bahan Humat dari Batubara tidak produktif dan Pupuk Buatan Terhadap Bibit Kakao (Theobroma cacao) pada Oxisol - Dewi rezki; Siska Efendi; Herviyanti (Jurusan Budidaya Perkebunan, 2022)
Organic matter has a very important role in determining the level of soil fertility, especially in marginal soils such as Oxisol which is widespread in Indonesia. Organic matter that is commonly used requires large amounts and has the ability to react relatively slowly in the soil. Therefore, it is necessary to make efforts to obtain organic material that reacts quickly in the soil, such as humic material extracted from lignite. In this study, cocoa (Theobroma cacao) was used as an indicator plant. Cocoa is one of the plantation commodities that has a fairly important role in the national economy, especially as foreign exchange for the country and has a relatively stable price. This research was conducted in the form of a pot experiment using a 2 x 4 x 4 factorial design with 3 replications in a divided plot design, so that 32 treatments and 96 experimental units were obtained. From the research results obtained data that the addition of humic materials and compost up to a dose of 4% C-organic combined with artificial fertilizers can increase the availability of nutrients for cocoa seedlings in Oxisol. The best dose of each treatment was the addition of humic material at a dose of 4% C-organic combined with artificial fertilizer 50% of the recommendation and the addition of compost at a dose of 4% C-organic combined with artificial fertilizer 50% of the recommendation. The addition of organic matter can reduce the use of artificial fertilizers up to 50% of the recommendation. The addition of humic materials from unproductive coal can increase the availability of nutrients in Oxisol. Unproductive coal has the potential to increase Oxisol soil fertility.